Band gap modification for enhancement in optoelectronic properties with silicon nanowire. (2021) - Kashyap, Vikas; Chaudhary, Neeru; Goyal, Navdeep; Saxena, Kapil
Abstract: Here, by varying the etching time of Si wafer with metal-assisted chemical etching process, we have formed the vertically aligned silicon nanowire (VA-SiNW) by etching the Si wafer for the duration of 40 min with metal-assisted chemical etching method. In this study Field-effect scanning electron microscopy has been used for the characterization of VA-SiNW (FESEM). Here the etching duration of 40 min has been used, the band gap modification has been analyzed by the use of photoluminescence spectroscopy. The study of photoluminescence spectroscopy (PL) and XRD offers proof of our findings and appears as supporting information. These 1-D nanostructures are quite influential in sensing, biological applications anti-reflection coating (ARC) properties and have broad use in electronic field.